Estudio comparativo de Frameworks (JAVA) ZK Y (PHP) LARAVEL para desarrollo de aplicaciones web y móviles. - Mosquera Coronel, Kevin Joffre (2022)
In this case study, a comparative analysis was carried out between LARAVEL and ZK Frameworks for web and mobile development, since the development of web applications has grown exponentially in recent years, and this is due to the fact that more applications are requested every day. for the web for which the Frameworks used with PHP and JAVA are identified, their characteristics and the benefits they provide to developer teams to carry out projects, it is essential to use tools that allow these applications to be implemented quickly and efficiently, in addition to being able to adapt to the needs of developers. Likewise, the model-view-controller software architecture pattern is discussed, also called MVC, the creation of components rendered in the view, the creation of a progressive web application, reaching a comparative analysis, including the characteristics of the specific frameworks, that is, ZK and LARAVEL, with their respective concepts and characteristics. Finally, this analysis aims to provide information to be able to choose the type of framework recommended for development, in which it is possible to identify the strengths and weaknesses of the Frameworks, and determine the most appropriate for development, whether for web or mobile, since Frameworks help us develop faster and not have to reinvent the wheel.